2020
DOI: 10.1108/jmd-11-2019-0451
|View full text |Cite
|
Sign up to set email alerts
|

Academic entrepreneurship intentions: a systematic literature review

Abstract: PurposeThe objective of this research is to have an up-to-date and comprehensive assessment of the current knowledge regarding the variables that encourage the individuals, within the academic community, to get involved in knowledge exploitation activities. It is influenced by the observation that there is a need for more systematic scrutiny of micro-level processes to deepen our understanding of academic entrepreneurship (Balven et al., 2018; Wright and Phan, 2018). The study proposes to answer to ‘What are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 128 publications
1
48
0
3
Order By: Relevance
“…This demonstrates that digital technologies enhances entrepreneurial startups among academics. Furthermore, Neves and Brito (2020) confirmed that the creation of spin-offs, patents and collaboration with industry are a consequence of scholars' engagement who, in turn, are influenced by the organisational and institutional structure. These findings posit that the university partially controls its outcomes.…”
Section: Opportunity In Actionmentioning
confidence: 70%
See 1 more Smart Citation
“…This demonstrates that digital technologies enhances entrepreneurial startups among academics. Furthermore, Neves and Brito (2020) confirmed that the creation of spin-offs, patents and collaboration with industry are a consequence of scholars' engagement who, in turn, are influenced by the organisational and institutional structure. These findings posit that the university partially controls its outcomes.…”
Section: Opportunity In Actionmentioning
confidence: 70%
“…In this regard, role models can also have a motivational impact (Radu & Loue, 2008) on choosing to become an entrepreneur. It would be interesting to propose some research within different contexts to understand if the academics who excel in scientific domains are also the most entrepreneurial hence indirectly linked with academics' personal attitude and perceived behavioural control (Neves & Brito, 2020). In this context, academic as technology researchers may demonstrate as influential role models in universities.…”
mentioning
confidence: 99%
“…The first paper of this special issue, written by Neves and Brito (2020) entitled “Academic entrepreneurship intentions: A systematic literature review”, offers a comprehensive assessment of the motives and intentions of scientists to get involved in knowledge exploitation activities. Based on a systematic literature review, this paper presents guidelines for building a scale of intentions assessment that may help universities and policy makers to further stimulate entrepreneurship activities as well as implement effective and value-driven policies.…”
Section: First Insights Into Micro-level Academic Entrepreneurshipmentioning
confidence: 99%
“…The second paper entitled “Entrepreneurial university: An exploratory model for higher education” (Ruiz et al 2020) by de Araujo et al (2020) focuses on the clarification of characteristics of entrepreneurial universities beyond the commercialisation of knowledge in the context of an entrepreneurial ecosystem. It thereby contributes to our understanding of the transformation of traditional universities towards entrepreneurial universities and serves as a starting point for empirical investigations.…”
Section: First Insights Into Micro-level Academic Entrepreneurshipmentioning
confidence: 99%
“…13 Moreover, researchers examined the determinants and outcomes of academic entrepreneurial intention. 14 Academic entrepreneurial intention is underscored by capability factors such as entrepreneurial-related abilities, education, human capital and industrial experience. 14 Academic Entrepreneurial Engagement (AEE) AEE entails the commercialisation of scientific knowledge, including the transformation of knowledge into products and processes that may inevitably contribute to economic growth and innovation.…”
Section: Introductionmentioning
confidence: 99%